Pengaruh Kecerdasan Emosional Dan Motivasi Kerja Terhadap Kinerja Pegawai Dengan Organizational Citizenship Behavior (OCB) Sebagai Variabel Intervening Pada Puskesmas Rawang Kota Padang - Nurul Fadhilah; Dori Mittra Candana; Mardhatila Fitri Sopali (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to examine the effect of emotional intelligence and work motivation on employee performance, with Organizational Citizenship Behavior (OCB) serving as an intervening variable at the Rawang Community Health Center in Padang City. A quantitative research approach was employed. Data were collected through observation and questionnaires. The sampling technique used was total sampling, involving 45 employees as respondents. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.The findings indicate that emotional intelligence has a positive and significant effect on Organizational Citizenship Behavior (OCB). Work motivation also has a positive and significant effect on OCB. Furthermore, emotional intelligence and work motivation each have a positive and significant effect on employee performance. Organizational Citizenship Behavior (OCB) is found to have a positive and significant effect on employee performance. However, OCB does not mediate the relationship between emotional intelligence and employee performance. In contrast, OCB successfully mediates the relationship between work motivation and employee performance.